Pro-math challenge goes to Ipoh / Anisah Abdul Rahman - Abdul Rahman, Anisah (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2019)
Universiti Teknologi MARA Perak Branch in collaboration with the Ministry of Education are working together to organize programmes that inspire better quality of life of the people through the mastery of science, technology and innovation. Its application focuses on emphasizing the education system in the fields of Science, Technology, Engineering and Mathematics (STEM). Organised by Faculty of Computer and Mathematical Sciences (FSKM), Pro-Math Challenge is a programme initiated, in conjunc-tion with STEM, to draw interest of school students in Mathematics. The theme of Pro-Math Challenge is 'Mathematical Application in Life' and in completing the challenge, the school students had to carry out simple and concise science experiments to improve under-standing of Mathematics and Science applications. During the ac-tivities, school students were exposed to basic calculation concepts, measurements which emphasize on the importance of precision and accuracy as well as the concept of probability.